2012
DOI: 10.1111/j.1755-3768.2012.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between components of newly diagnosed exudative age‐related macular degeneration lesion and focal retinal sensitivity

Abstract: ABSTRACT.Purpose: To analyse lesion components determining retinal sensitivity in microperimetry in eyes with newly diagnosed exudative age-related macular degeneration (AMD).Methods: Visual acuity, contrast sensitivity, microperimetry, optical coherence tomography (OCT), and fluorescein (FA) and indocyanine green (ICGA) angiographies of 23 eyes of 23 patients were analysed. Central microperimetry grids with 28 test stimulus sites were automatically aligned with three-dimensional OCTs and manually aligned with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The results of our study suggest that the iPad application is able to detect differences in retinal sensitivity related to the underlying pathologic changes associated with AMD, similar to that reported with formal microperimetry. 29 32 When looking at our cohort of treatment eyes with nAMD, we noticed a general lower mean retinal sensitivity of 24.1 dB compared to the at-risk fellow eye (28.8 dB). While sensitivity associated with areas of atrophy, RPE disturbance, and absent EZ had significant reductions in mean retinal sensitivities ( Table 5 ), we were unable to show significant reduced sensitivity in areas with IRF and SRF compared to an averaged nAMD eye.…”
Section: Discussionmentioning
confidence: 84%
“…The results of our study suggest that the iPad application is able to detect differences in retinal sensitivity related to the underlying pathologic changes associated with AMD, similar to that reported with formal microperimetry. 29 32 When looking at our cohort of treatment eyes with nAMD, we noticed a general lower mean retinal sensitivity of 24.1 dB compared to the at-risk fellow eye (28.8 dB). While sensitivity associated with areas of atrophy, RPE disturbance, and absent EZ had significant reductions in mean retinal sensitivities ( Table 5 ), we were unable to show significant reduced sensitivity in areas with IRF and SRF compared to an averaged nAMD eye.…”
Section: Discussionmentioning
confidence: 84%
“…With the use of fmERG, Nishihara et al reported that, in eyes with neovascular AMD, the amplitude of each wave was reduced to 29% to 35% of that of the control eyes [26]. With the use of microperimetry, Sulzbacher et al [24] and Hautamäki et al [27] reported more recently that retinal sensitivity was markedly decreased within the area of CNV, macular edema, hemorrhage, subretinal fluid, or PED in eyes with neovascular AMD. In our patients with neovascular AMD, cystoid macular edema was seen in 21%, serous retinal detachment was seen in 74%, and PED was seen in 89% of the patients, and thickness of the fovea in the neurosensory retina was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Microperimetry was undertaken by the Nidek MP1 or MP1-S in 29 of the 52 included articles 3,5,9,12,16,17,23,25,[32][33][34][35]39,41,43,45,48,49,51,52,[55][56][57][59][60][61][62][63]68 by the Nidek MP3 in 1 27 , by the MAIA in 13 4,6,11,65,[69][70][71][72][73][74][75][76][77] , by the Optos Spectral OCT/SLO in 7 13,20,[28][29][30]38,53 and by the Rodenstock SLO microperimeter in two articles 18,…”
Section: Quality Of Evidencementioning
confidence: 99%
“…Fifteen included studies used microperimetry alongside other measures of visual function in individuals with AMD 3,5,11,18,23,30,43,45,48,49,56,69,71,72,77 .In early AMD (International Classification to a lesser extent, with reading speed (r=0.37 all p<0.001) 56 . In those undergoing anti-VEGF treatment, however, no association was present between the MS and either VA or CS 30,43 .…”
Section: Microperimetry and Other Measures Of Visual Functionmentioning
confidence: 99%